Tongue microbiota in relation to the breathing preference in children undergoing orthodontic treatment - Zuzana Marincak Vrankova; Petra Brenerova; Lenka Bodokyova; Jan Bohm; Filip Ruzicka; Petra Borilova Linhartova (BMC, 2024)
Abstract Background Mouth breathing (MB), a risk factor of oral dysbiosis and halitosis, is linked with craniofacial anomalies and pediatric obstructive sleep apnea. Here, we aimed to analyze tongue microbiota in children from the perspective of their breathing pattern before/during orthodontic treatment. Methods This prospective case-control study included 30 children with orthodontic anomalies, 15 with MB and 15 with nasal breathing (NB), matched by age, sex, and body mass index. All underwent orthodontic examination and sleep apnea monitoring. Tongue swabs were collected before starting (timepoint M0) and approx. six months into the orthodontic therapy (timepoint M6). Oral candidas and bacteriome were analyzed using mass spectrometry technique and 16S rRNA sequencing, respectively. Results MB was associated with higher apnea-hypopnea index. At M0, oral candidas were equally present in both groups. At M6, Candida sp. were found in six children with MB but in none with NB. No significant differences in bacterial diversity were observed between groups and timepoints. However, presence/relative abundance of genus Solobacterium was higher in children with MB than NB at M0. Conclusions Significant links between MB and the presence of genus Solobacterium (M0) as well as Candida sp. (M6) were found in children with orthodontic anomalies, highlighting the risk of halitosis in them.